The adoption of blended learning using Coursera MOOCs: A case study in a Vietnamese higher education institution - Thao Ho, Nguyen Thi; Pham, Hiep-Hung; Sivapalan , Subarna; Dinh, Viet-Hung (Australasian Journal of Educational Technology, 2022)
This research is unique to a Vietnamese higher education institution that adopted blended learning using Coursera MOOCs. Employing the service quality model, the objective was to investigate factors affecting the continuance intention and recommendation to others towards blended learning using Coursera MOOCs. This study was conducted an online survey with 637 students across four campuses of a Vietnamese higher education institution. The results of the structural equation modeling showed that the learning content and online responsiveness increased satisfaction with Coursera MOOCs whereas online reliability did not affect satisfaction with Coursera MOOCs. There were also positive relationships between empathy, tangibles, classroom responsiveness, and classroom activities. Assurance and classroom reliability had no significant impacts on classroom activities. Satisfaction and classroom activities positively influenced the continuance intention towards blended learning using Coursera MOOCs. Lastly, satisfaction, classroom activities, and continuance intention significantly affected the recommendation to others towards blended learning using Coursera MOOCs. Implications for practice or policy: A case study process for evaluating the quality of the blended learning using Coursera MOOCs is detailed. Practical recommendations are made for curriculum development, teaching and learning, assessment, and professional development as universities implement the blended learning using MOOCs.